Brief EcoMeditation Associated With Psychological Improvements: A Preliminary Study. (December 2020) - Church, Dawson; Stapleton, Peta; Sabot, Debbie
Background: A growing body of clinical research attests to the psychological and physiological benefits of meditation. EcoMeditation is a non-pharmacological therapeutic approach used to promote health and well-being, comprising four evidence-based techniques: The Quick Coherence Technique for regulating heart rate variability (HRV), Emotional Freedom Techniques (EFT), mindfulness, and neurofeedback. Objectives: This study investigated changes in psychological symptoms of anxiety, depression, posttraumatic stress disorder (PTSD), pain, and happiness following a one-day EcoMeditation training workshop delivered in a large-group format and at 3-months post-intervention. Methods: A convenience sample of 208 participants (137 women, 71 men) aged between 21 and 87 years ( M  = 55.4 years; SD  = 12.8 years) attended a one-day EcoMeditation training workshop. Participants completed a pen-and-paper survey pre-workshop and post-workshop, and an online survey three months following the EcoMeditation intervention. Results: Post-workshop results revealed significant reductions in anxiety (−23.4%, p  <   .001), depression (−15.8%, p  =   .011), PTSD (−11.8%, p  <   .001), and pain (−18.5%, p  <   .001), while happiness scores increased significantly (+8.9%, p  <   .001). At 3-month follow-up, one-way repeated-measures ANOVA ( N  =   65) found significant decreases in anxiety between pre-test and post-test, and pain between pre-intervention and 3-month follow-up. Differences in depression and PTSD scores were not significant over time. Happiness scores significantly increased from pre-test to 3-month follow-up. However, post-hoc analyses suggested that the final sample size was inadequate to detect significant differences between time points. Conclusion: Findings provide preliminary support for EcoMeditation as a brief group-based stress reduction intervention with benefits for improved psychological functioning.